The Effect of Vocabulary Mastering And Reading Habits on The Ability of Writing Description Texts - Rizky Mirani Desi Pratama; Dwi Puji Hastuti; Wiruma Titian Adi (LPPM Universitas Bina Sarana Informatika, 2022)
The research aims to determine the effect of vocabulary mastery on students' English descriptive writing skills and the impact of reading habits on students' English descriptive writing skills, as well as the effect of vocabulary mastery and reading habits together on students' English descriptive writing skills. The population in this study was students of class X State Senior High School in Cibinong and the sample was 120 students. The sampling technique was processed using a simple random sampling method. Descriptive statistical methods were used in this research. The research instrument used was a questionnaire on students' vocabulary mastery, reading habits, and a descriptive text writing skill test. Data analysis used SPSS version 25, the significant level of = 0.05. The requirement analysis use normality test, homogeneity test, two-way ANOVA. The result of this research is vocabulary mastery by the value of sig. = 0.77 < 0.05 does not have a significant effect on students' descriptive text writing skills, reading habits have a significant influence on students' descriptive text writing skills by the value of sig. = 0.01 < 0.05 and there is no significant effect of vocabulary mastery and reading habits on students' writing skills by the value of sig. = 0.01 < 0.265.